Gender and History Ireland, 1852-1922 - ATWAL, JYOTI; Breathnach, Ciara; Buckley, Sarah-Anne (Taylor & Francis, 2023)
This book provides an overview of Irish gender history from the end of the Great Famine in 1852 until the foundation of the Irish Free State in 1922. It builds on the work that scholars of women's history pioneered and brings together internationally regarded experts to offer a synthesis of the current historiography and existing debates within the field. The authors place emphasis on highlighting new and exciting sources, methodologies, and suggested areas for future research. They address a variety of critical themes such as the family, reproduction and sexuality, the medical and prison systems, masculinities and femininities, institutions, charity, the missions, migration, 'elite women', and the involvement of women in the Irish nationalist/revolutionary period. Envisioned to be both thematic and chronological, the book provides insight into the comparative, transnational, and connected histories of Ireland, India, and the British empire. An important contribution to the study of Irish gender history, the volume offers opportunities for students and researchers to learn from the methods and historiography of Irish studies. It will be useful for scholars and teachers of history, gender studies, colonialism, post-colonialism, European history, Irish history, Irish studies, and political history.